Risk Difference of Multidrug Resistance Organisms (MDROs) According to Risk Factor and Hand Hygiene Compliance - Ajeng FS Kurniawati; Prijono Satyabakti; Novita Arbianti (Jurnal Berkala Epidemiologi, 2015)
Nosocomial infection is still a global public health problem. At the same time, there is a problem of bacterial resistance to several classes of antibiotics called multidrug resistance organisms (MDROs). The incidence of MDROs is higher in the Intensive Care Unit (ICU) compared to other service units. Bacterial transmission can be prevented by hand hygiene. The purpose of this study is to analyze the differences in the risk of MDROs according to risk factors and compliance with hand hygiene. This study uses a case-control design with a sample size of 20 in each case and control group. Case samples were MDROs patients at ICU “Y“ Hospital (RS “Y”) Surabaya, while the control sample was ICU “Y” Hospital Surabaya patients who were not MDROs. The independent variable is the duration of use of antibiotics, length of stay, use of ventilator medical devices and compliance with hand hygiene of health workers. Data analysis uses the Odds Ratio (OR) and Risk Difference (RD) analysis. The results showed that the difference in the risk of MDRO infection was based on the duration of antibiotic use (OR=10,23; 95%CI=1,12<OR<93,35; RD=0,47), length of stay (OR=7,36; 95%CI=1,34<OR<40,55; RD=0,44), use of a ventilator medical device (OR=9,00; 95%CI=1,64<OR<49,45; RD=0,48), and hand hygiene compliance (OR=6,00; 95% CI=1,46<OR<24,69; RD=0,42). Based on the results of the study, it can be concluded that maintaining hygiene before taking medical measures, including tools, environment and health workers' bodies must be carried out so that they do not become a medium for the growth of MDRO bacteria.